2018
DOI: 10.1038/s41598-018-28163-w
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Glyphosate Resistance in Conyza canadensis from Agricultural and Non-Agricultural Sites in Ohio and Iowa

Abstract: Glyphosate is an important herbicide worldwide, but its efficacy has been compromised where weed species have evolved glyphosate resistance. To better understand evolutionary outcomes of continued and strong selection from glyphosate exposure, we characterized variation in resistance in self-pollinating Conyza canadensis (horseweed) in Ohio and Iowa, where glyphosate resistance was first reported in 2002 and 2011, respectively. In 2015, we collected seeds from a total of 74 maternal plants (biotypes) from no-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…As noted above, we assumed that seeds from the same maternal plant were full sibs and we referred to these maternal seed families as individual biotypes. In a previous study, we confirmed that progeny from the same maternal plant had consistent levels of resistance to glyphosate (Beres, Ernst, et al, ). Here, we used common garden experiments to compare fitness‐related traits among a subset of the 74 biotypes described in Beres, Ernst, et al ().…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…As noted above, we assumed that seeds from the same maternal plant were full sibs and we referred to these maternal seed families as individual biotypes. In a previous study, we confirmed that progeny from the same maternal plant had consistent levels of resistance to glyphosate (Beres, Ernst, et al, ). Here, we used common garden experiments to compare fitness‐related traits among a subset of the 74 biotypes described in Beres, Ernst, et al ().…”
Section: Methodssupporting
confidence: 84%
“…In a previous study, we confirmed that progeny from the same maternal plant had consistent levels of resistance to glyphosate (Beres, Ernst, et al, ). Here, we used common garden experiments to compare fitness‐related traits among a subset of the 74 biotypes described in Beres, Ernst, et al (). Seeds were collected from one maternal plant per population from both agricultural and nonagricultural habitats in southern Iowa in 2015 (Figure ).…”
Section: Methodssupporting
confidence: 84%
See 3 more Smart Citations